PENERAPAN PEMBELAJARAN AKTIF TIPE TRUEOR FALSE STATEMENT UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 36 PADANG TAHUN PELAJARAN 2012/2013 - Sari, Hendrika Milta; Indriati, Gustina; Maizeli, Annika (STKIP PGRI Sumbar, 2013)
ABSTRACT The less studententhusiasm for learningresulted inmanyof hisstudentswhoare lessactivein following thebiologicallearning process. Students whoare active inthe learningprocessis thefollowingstudents whohavehighacademic ability, while studentswhohavelow academicabilityonlyacceptinformation submittedby the teacher. The less student understandingof the materialpresented by the teacherresulted inlow yieldsbiological spending the36eighth grade students ofSMPNPadangAcademic Year2012/2013. Still below the minimum completeness criteria (KKM) is 70. One alternative to overcome this problem is the application of active learning statemant type true or false. This study aims to improve the results of biological studies at the Junior High School eighth grade students in the Academic Year 36 Padang 2012/2013.This type of research is experimental research. The population in this study were 36 eighth grade students of SMPN Padang Academic Year 2012/2013 consisting of 3 classes. Sampling using purposive sampling, in order to obtain samples of the 2-class class VIII.3 as VIII.1 as experimental and control classes.The instrument usedwas atestof student learning out comesandthe averagevalues obtainedexperimental class70,95 andclasscontrol 59,62. Techniques of data analysis is the average similarity by testing t-test at the 0.05 significance level. The results of the data analysis obtained while the price t 2.89 1.70 t table. This means t count> t table, so the hypothesis is accepted. From this study it can be concluded that the application of learning strategies statement true or false can improve learning outcomes biology class VIII SMPN 36 Padang academic year 2012/2013.